Access Without Usage: The Persistence of Cash in Morocco - Hamid RAFIK,; Hicham LEMAALLEM, (African Scientific Journal, 2026)
Abstract Morocco has built a modern retail-payment system—more than twenty-two million bank cards, an interoperable interbank switch in place since 2004, a regulated mobile-payment regime, and near-universal mobile access—yet the overwhelming majority of transactions are still settled in cash, and currency in circulation has climbed to roughly 29 percent of GDP, well above its pre-pandemic norm and among the highest ratios in the world. This paper documents the paradox and argues that it is best understood not as a transitional lag awaiting more infrastructure but as a rational equilibrium. The methodological approach combines a structured reading of the aggregate payment series with international benchmarking, and interprets the resulting regularities through four analytical lenses drawn from the economics of informality, two-sided markets, institutional trust, and financial-inclusion design. The sample consists of the aggregate retail-payment statistics published by Bank Al-Maghrib and the Centre Monétique Interbancaire for 2019–2024—card withdrawals, card payments to merchants and online, mobile-wallet accounts and transactions, and currency in circulation—together with World Bank Global Findex survey data for Morocco in 2017 and 2021 and a benchmark set of five comparator economies (Sweden, Türkiye, Brazil, India, and Kenya) alongside regional aggregates. Drawing on descriptive payment statistics and international benchmarking, we establish four stylized facts—cards used mainly to withdraw cash, adoption confined to small-value payments, a rising cash-to-GDP ratio, and access without usage—and show that several economies poorer than Morocco have moved far further toward digital payment, so income does not bind. We trace the persistence to four mutually reinforcing frictions: a large cash-based informal sector, the two-sided economics of merchant acceptance, weak recourse and trust that make digital payment a credence good, and an access-focused inclusion policy. Comparison with Brazil, India, and Kenya indicates that the equilibrium shifts only when digital rails become instant, free at the point of use, interoperable, and account-to-account, and a coordinating force resolves the chicken-and-egg of two-sided adoption. The goal, we conclude, is not a war on cash but lowering the relative cost of the digital option until the merchant side tips. More broadly, Morocco’s experience points to a lesson about sequencing: building bank-based card rails first can entrench cash in ways that economies leapfrogging to instant, account-to-account rails avoided. The principal conclusion is that Morocco’s binding constraint lies on the merchant side and in the institutions surrounding payment rather than in the quantity of infrastructure, so that the effective policy lever is the relative cost of the digital option—acceptance pricing, a unified point-of-sale standard, credible recourse, and a coordinating force capable of moving both sides of the market together. Keywords: cash; digital payments; financial inclusion; payment systems; two-sided markets; informal economy; mobile money; Morocco.